Ethnobotanical Survey on Antidepressive Plants Used for Mood Management in Algeria - Gadouche, Leila; Zidane, Azdinia; Mokhtari, Djamel E.; Metlef, Sarra; Aichouni, Ahmed (Zeitschrift für Phytotherapie, 2024)
Depression is a mood disorder associated with cognitive decline. To self-medicate, people use medicinal herbs to limit the side effects associated with taking antidepressants, such as addiction, hallucinations, and dizziness. Current research consists of ethnobotanical studies of medicinal plants used to improve depression-related mood disorders, and the socio-economic profiles of people with depression (gender, age, education level…) and information about the listed antidepressant plants (common name, part used…). 129 individuals belonging to some regions of Algeria answered our questionnaire among which 82% are women and 98% are academics. The informants cited 44 species (Mentha spicata with a relative frequency of citation (RFC) =0.69, Chamomilla nobilis RFC=0.49, Aloysia citrodora RFC=0.19, Lavandula officinalis, Melissa officinalis RFC=0.17, Foeniculum vulgare RFC=0.1, Pimpinella anisum RFC=0.09 and Hypericum perforatum RFC=0.07…) belonging to 25 botanical families represented mainly by the Lamiaceae family (38%). Infusion remains the most common method of preparation, and the leaves are the most used part. These plants modulated the depressive state of informants in a similar way to synthetic antidepressants. These plants deserve to be studied for the development of new herbal drugs with acceptable side effects.